Crystallographic texture of straight‐rolled α‐uranium foils via neutron and X‐ray diffraction. Issue 3 (25th May 2017) - Einhorn, J. R.; Steiner, M. A.; Vogel, S. C.; Garlea, E.; Agnew, S. R.
Abstract : The bulk and surface textures of recrystallized straight‐rolled α‐uranium foils are established by both neutron and X‐ray diffraction and discussed relative to the existing literature on α‐uranium processing textures. Abstract : The texture of recrystallized straight‐rolled α‐uranium foils, a component in prospective irradiation target designs for medical isotope production, has been measured by neutron diffraction, as well as X‐ray diffraction using both Cu and Mo sources. Variations in the penetration depth of neutron and X‐ray radiation allow for determination of both the bulk and surface textures. The bulk α‐uranium foil texture is similar to the warm straight‐rolled plate texture, with the addition of a notable splitting of the (001) poles along the transverse direction. The surface texture of the foils is similar to the bulk, with an additional (001) texture component that is oriented between the rolling and normal directions. Differences between the surface and bulk textures are expected to arise from shear forces during the rolling process and the influence that distinct strain histories have on subsequent texture evolution during recrystallization.